Il canto e la liturgia: riflessioni musicologiche fra prassi musicali e prescrizioni ecclesiastiche (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: Premessa - 1. Canto e liturgia - 2. Dal canto gregoriano al canto piano - 3. La musica figurata, l’organo, le cappelle musicali.Chant and music in the liturgy: musicological observations between musical practice and ecclesiastical regulations *ABSTRACT: Chant, polyphony, the role of the organ, and other forms of music performed in the liturgy are examined from the middle ages to the early modern era in order to point out ecclesiastical regulations and possible legislation.